Phase transitions and symmetry energy in nuclear pasta - Dorso, Claudio Oscar (2018)
Cold and isospin-symmetric nuclear matter at sub-saturation densities is known to form the so-called pasta structures, which, in turn, are known to undergo peculiar phase transitions. Here we investigate if such pastas and their phase changes survive in isospin asymmetric nuclear matter, and whether the symmetry energy of such pasta configurations is connected to the isospin content, the morphology of the pasta and to the phase transitions. We find that indeed pastas are formed in isospin asymmetric systems with proton to neutron ratios of x = 0.3, 0.4 and 0.5, densities in the range of 0.05 fm−3 < ρ < 0.08 fm−3, and temperatures T < 2 MeV. Using tools (such as the caloric curve, Lindemann coefficient, radial distribution function, Kolmogorov statistic, and Euler functional) on the composition of the pasta, determined the existence of homogeneous structures, tunnels, empty regions, cavities and transitions among these regions. The symmetry energy was observed to attain different values in the different phases showing its dependence on the morphology of the nuclear matter structure.